2000
DOI: 10.1093/molehr/6.7.648
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the cyclic AMP-dependent transcription factors, CREB, CREM and ATF2, in the human myometrium during pregnancy and labour

Abstract: Elevated concentrations of cyclic AMP (cAMP) in the human myometrium may promote uterine quiescence during pregnancy by protein kinase A (PKA)-mediated phosphorylation and subsequent inactivation of myosin light-chain kinase, as well as by the phosphorylation and activation of cAMP-dependent transcription factors. In this context, we show that the altered expression of cAMP response-element binding protein (CREB), cAMP response-element modulator protein (CREM) and activating transcription factor 2 (ATF2) are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 55 publications
2
20
1
Order By: Relevance
“…Our previous results indicate that in vivo, at some point during pregnancy, expression of ATF2 is downregulated in the myometrium whereas ATF2-sm becomes spatially expressed with greater levels detected in the fundus compared with the lower uterine segment (Bailey et al 2000). These events may consequently have major effects on the genes observed to be regulated by these proteins in this study.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Our previous results indicate that in vivo, at some point during pregnancy, expression of ATF2 is downregulated in the myometrium whereas ATF2-sm becomes spatially expressed with greater levels detected in the fundus compared with the lower uterine segment (Bailey et al 2000). These events may consequently have major effects on the genes observed to be regulated by these proteins in this study.…”
Section: Discussionsupporting
confidence: 47%
“…It is therefore interesting to note the increased expression of oestrogen receptor 2 (ESR2/ESR-beta) with over-expression of ATF2, and to compare this to the detected increase in expression of the alternative oestrogen receptor 1 (ESR1/ESR-alpha) associated with over-expression of the ATF2-related bZIP transcription factor CREB in myometrial cells (Bailey et al 2004), which has been found to be prevalent in the non-pregnant myometrium but almost absent in pregnant non-labouring and spontaneous labouring tissue (Bailey et al 2000). Interestingly, a significant minority of genes found to be affected by the over-expression of ATF2 and ATF2-sm in myometrial cells in this study are also affected by CREB (Bailey et al 2004): 25% of the genes affected by ATF2, and 38% of the genes affected by ATF2-sm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in PDGF activates Cx43 promoter in the presence of cAMP. Previous studies have demonstrated the presence of activator protein-1 (AP-1) and CRE in the promoter region of Cx43 (2,7,24). Because PDGF and IBMX are well-known activators of AP-1 and CRE, respectively, the agents may upregulate Cx43 via activation of these regulatory elements.…”
Section: Effect Of Pdgf-bb On Cx43 Expression Is Not Attributable To mentioning
confidence: 99%
“…It is clear, however, that components of the cAMP/protein kinase A (PKA) pathway are differentially expressed in the human myometrium during pregnancy (41)(42)(43)(44)(45)(46)(47): central to this is the GTP-binding protein G␣ s . Indeed, signaling through G␣ s is thought to facilitate promotion of myometrial quiescence, and G␣ s protein levels have been shown to be reduced at the onset of labor (41,42).…”
mentioning
confidence: 99%